Empowering the Arabic – Javanese translation as an indigenous language protection in Asia toward the books of Islamic moral ethic - Anis, Muhammad Yunus; Arifuddin, Arifuddin; Farhah, Eva; Malik, Abdul (citeus, 2016)
This article was undertaken to investigate the moral ethics learned in the Arabic-Javanese translation text, and how this model of translation can be the main aspect of protecting the indigenous/natural/mother language in Indonesia as a main potential of Asian Cultural Heritage. The data of this research is a Arabic – Javanese translation texts and also some units of language inside the texts. The result of this article shows that there is a connection line between empowering of Arabic Javanese translation and protecting the indigenous language.